Synthesis of thiosemicarbazone derivatives and evaluation of their cytotoxicity with emphasis on ferroptosis biomarkers; an in vitro study - Yasaman Shadmani; Yaghoub Pourshojaei; Somayyeh Karami-Mohajeri; Bagher Amirheidari; Motahareh Sadeghzadeh (Research in Pharmaceutical Sciences)
Background and purpose: This study aimed to evaluate the cytotoxicity of synthesized thiosemicarbazone derivatives, particularly on biomarkers associated with ferroptosis. Experimental approach: Thiosemicarbazone derivatives (C1-C5) were synthesized by condensation between thiosemicarbazide and the corresponding benzaldehyde derivatives. The compounds were characterized using IR spectroscopy and H/C NMR spectroscopy. To evaluate their biological activity, PC-12 cells were cultured in DMEM/MEM medium supplemented with 10% bovine serum albumin. Cell viability was assessed using the MTT assay, while intracellular reactive oxygen species (ROS) levels were measured using DCFH-DA. Additionally, glutathione peroxidase (GPX) activity, lipid peroxidation (LPO), and total antioxidant capacity (TAC) were evaluated to determine oxidative stress and antioxidant response. Findings/Results: In cell viability assessments, C2 exhibited the highest toxicity, while C4 demonstrated the lowest toxicity after 24 h. Among all derivatives, only C3 reduced ROS levels without affecting GPX activity. All derivatives effectively reduced LPO, although C5 showed the least effectiveness in this regard. In contrast to C2 and C5, TAC was significantly higher than the control after treatment with C1, C3, and C4. Conclusion and implications: These findings suggest that thiosemicarbazone derivatives may influence the ferroptosis cell death pathway through their chelation properties, necessitating further research on their ability to bind to iron. Their effects on oxidative stress and cellular antioxidant capacity provide valuable insights for therapeutic strategies.